Selectivity of Bacillus thuringiensis (Bacillales: Bacillaceae) to the polyphagous predator Ceraeochrysa claveri (Navás, 1911) (Neuroptera: Chrysopidae) - Daquila, Bruno Vinicius; Moi, Dieison André; Scudeler, Elton Luiz; Oliveira, João Arthur dos Santos; Polanczyk, Ricardo Antonio; Conte, Helio (Wiley, 2023)
Bioinsecticides based on Bacillus thuringiensis (Bt) are widely used to control agricultural pests. However, there are concerns about their impact on non-target organisms, with for example, the green lacewing Ceraeochrysa claveri, a polyphagous predator with important value in the biological control of insect pests in agroecosystems. This study aimed to analyse the effects of Agree® bioinsecticide (containing Bt serovar aizawai GC-91) on the post-embryonic development of C. claveri. For this, neonate larvae of C. claveri were fed with Diatraea saccharalis eggs contaminated with different concentrations of Agree® (0.62, 1.25, 2.50 and 5.00 g L−1) until their pupation. Samples of the midgut of larvae were collected for histological and ultrastructural analysis. The larval and pupal inviability data were collected at the end of the respective developmental stages. After the emergence of adult insects, were considered inviable those with morphological alterations. To evaluate the reproduction, adult insect couples were formed, and the oviposition was collected. No significant differences in the viability of eggs, larvae, pupae and adults of C. claveri contaminated with Agree® were reported. Midgut analyses did not reveal cellular damage in the epithelium, indicating a possible lack of insecticidal proteins receptors. The oviposition and their viability were similar between treated and control groups. Our results demonstrated that Agree® bioinsecticide did not affect the post-embryonic development of C. claveri. This illustrates that the combined use of Bt and C. claveri for the biological control of arthropod pests can be a sustainable strategy for integrated pest management.
Keywords: agroecosystems; biological control; Bt; environmental management; green lacewing; insects; sustainability